Capecitabine after Surgical Salvage in Recurrent Squamous Cell Carcinoma of Head and Neck. (December 2017) - Manohar, Poorni M.; Sapir, Eli; Bellile, Emily; Swiecicki, Paul L.; Pearson, Alexander T.; Prince, Mark E.; Shuman, Andrew G.; Bradford, Carol R.; Chepeha, Douglas B.; Wolf, Gregory T.; Eisbruch, Avraham; Worden, Francis P.; et al.
Due to the high incidence of recurrent squamous cell carcinoma of the head and neck and the toxicity profile of current salvage regimens, there is a need for tolerable and effective treatment options. We performed a retrospective matched case series to report our experience with recurrent high-risk patients who received capecitabine (CAP) therapy in the adjuvant setting after salvage therapy. The 5-year recurrence-free survival rates for the CAP and control cohorts were 54% (95% CI, 0.27%-0.75%) and 27% (95% CI, 0.09%-0.50%), respectively. Multivariable Cox modeling showed a significant improvement in recurrence-free survival in the CAP cohort (hazard ratio, 0.19; 95% CI, 0.04-0.92; P = .0392). While this was a respective analysis that could not control for all variables, these exploratory findings offer insights that may inform a prospective study to determine CAP efficacy.